Audouin's gull Larus audouinii, a new breeding gull species in the Adriatic sea (Croatia) - Rubinič, Borut (Acrocephalus, 2000)
The last reliable information on the occurrence of Audouin's Gull Larus audouinii in the Adriatic dates back to the end of the 19th century. The nestsites nearest to the area described herewith are those on the Apulian coast (Italy) and in the Aegean Sea (Greece). The present article deals with the new breeding area discovered in the Adriaric on some islets and rocks around the island of Korčula (S Dalmatia, Croatia). Here, the Audouin's Gull was recorded for the first time on July 19th 1996, when 4 birds were observed at sea off the village of Duba on Pelješac Peninsula. In the springs of 1997 and 1998, the authors surveyed 29 islets and rocks in the area covering some 700 km2. In 1997, 7 breeding pairs on 6 islets were recorded, while in 1998 6 pairs were registered on 5 islets. Audouin's Gulls were seen moscly in pairs, and courtship activity by a male was also noted. The Audouin's Gulls breeding in colonies together with the Yellow-legged Gulls Larus cachinnans were more aggressive than those breeding separately During the research, a nest was alsofound, while on July 21st 1997 a juvenile Audouin's Gull was sighted on the SW coast of Korčula. The authors believe that Audouin's Gull could also breed on some other islands along the Dalmatian coast in Croatia.
Keywords: bird; Birds; ptice; ornitologija; Ecosystem; galebi; Nesting behavior; Croatia